Management accounting in a supply chain environment: case study insights / Noriza Mohd Jamal and Mike Tayles - Mohd Jamal, Noriza; Tayles, Mike (2010)
As companies become involved in inter-organizational supply chains and the 'boundaries' of the organisation changes, the implications for cost and management accounting are increasingly important. In the recent management accounting literature, increased attention is being given to the role management accounting (MA) information plays within supply chain relationships. However, attempts to systematically relate supply chain management (SCM) to management accounting practices (MAP) have been limited. In this paper, we investigate companies' SCM practices and relate these to MA practices. Data was collected from semi structured interviews with senior managers of two international quoted companies in Malaysia. Managers' views of how SCM influences MA practices were sought. The findings suggest that the sophistication level of management accounting practices varies with SCM practices. Further analysis reveals that the interviewees differ in their views of how SCM affects MA.